1996
DOI: 10.1073/pnas.93.11.5472
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi apparatus of spinal cord motor neurons in transgenic mice expressing mutant Cu,Zn superoxide dismutase becomes fragmented in early, preclinical stages of the disease.

Abstract: Dominant mutations of the SOD] gene encoding Cu,Zn superoxide dismutase have been found in members of certain families with familial amyotrophic lateral sclerosis (ALS). To better understand the contribution of SODI mutations in the pathogenesis of familial ALS, we developed transgenic mice expressing one of the mutations found in familial ALS. These animals display clinical and pathological features closely resembling human ALS. Early changes observed in these animals were intra-axonal and dendritic vacuoles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
188
2
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(210 citation statements)
references
References 41 publications
19
188
2
1
Order By: Relevance
“…Mutant SOD1 induces eR stress [6] and Golgi fragmentation [26] in neuronal cell cultures, and we now show that aggregated SOD1 Wt induces UPR and Golgi fragmentation similar to mutant SOD1. these findings are consistent with recent evidence for common pathogenic pathways shared by mutant SOD1 and SOD1 Wt , and the presence of misfolded SOD1 Wt in sporadic aLS tissues [4,5].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Mutant SOD1 induces eR stress [6] and Golgi fragmentation [26] in neuronal cell cultures, and we now show that aggregated SOD1 Wt induces UPR and Golgi fragmentation similar to mutant SOD1. these findings are consistent with recent evidence for common pathogenic pathways shared by mutant SOD1 and SOD1 Wt , and the presence of misfolded SOD1 Wt in sporadic aLS tissues [4,5].…”
Section: Discussionsupporting
confidence: 59%
“…We also confirm here that intracellular mutant SOD1 inhibits the transport of VSVG-ts045 from the eR to Golgi in Sh-SY5Y cells, and we show that extracellular forms of mutant and aggregated SOD1 Wt also delay eR-Golgi traffic, thus providing one possible explanation for induction of eR stress. Similarly, Golgi fragmentation is also triggered by an imbalance between anterograde and retrograde traffic between eR and Golgi [26], highlighting a possible role for disruption to eR-Golgi traffic in both events. the activation of pro-apoptotic ChOP and increase in the proportion of cells undergoing apoptosis in cells treated with extracellular SOD1 provides a link between extracellular proteins and neurodegeneration and UPR-specific cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutated Cu,Zn-SOD have several enhanced activities that could be capable of selectively damaging interacting proteins or their associated organelles (5,24,36,38). Investigators at our laboratory previously reported that Cu-binding affinities are decreased in mutated Cu,Zn-SOD (26) and mutated Cu,Zn-SOD are highly susceptible to nonenzymatic glycosylation, i.e., glycation (34).…”
Section: Discussionmentioning
confidence: 99%
“…1 A Lower). Because there is evidence for early commencing noxious effects of mutant hSOD1s in spinal cords (7,(10)(11)(12), the G93A transgenic mice were examined from birth until death. The high proportion (Ϸ3%) of HIC-binding hSOD1 in spinal cord was seen from birth throughout life.…”
Section: The Hic-binding Hsod1 Is Enriched In the Spinal Cords In Thementioning
confidence: 99%